Zmiany zagospodarowania rynku w Szadku w drugiej połowie XX w. - Kowara, Sylwia (Biuletyn Szadkowski, 2012)
Szadek is a town of medieval origin, established in the early 12th century. At the time when it was granted city rights it acquired both new features and a new spatial arrangement with a four-sided square in its center. This square, along with the building frontages, still constitutes a major urban interior, whose characteristics substantially influence the perception of the city. This article aims to show changes in the spatial development of Szadek square over the last half century. During this period its appearance, the manner it is used and its functions have undergone substantial changes. The reason for this transformation is that the town square played in the early postwar years the role of a market place where markets were held weekly, while now it functions as a representative central meeting place for recreation, and its paved surface is now transformed into a square filled with greenery.